Analyzing the effectiveness of marketing tactics and human resource management practices in Berger Paints Bangladesh Ltd. - Tahlin, Nabila (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.